Assessing teaching quality in nutrition education: A study of two programs in the Netherlands and Australia - Angeliek Verdonschot (Elsevier, 2021)
The quality with which teachers deliver school-based nutrition programs may impact program effectiveness. The current study examined teaching quality of two programs, Taste Lessons (n = 15 Grade 6 and 7 teachers) and CUPS (n = 3 Year 3 and 4 teachers) via lesson observation using the Quality Teaching Model (QTM). Taste Lessons is a well-established Dutch program on healthy eating and CUPS is a novel Australian program that contains lessons in which nutritional content is integrated with mathematical concepts. The QTM evaluates three dimensions of teaching (Intellectual Quality, Quality Learning Environment and Significance), each containing six elements of classroom practice. Each element was coded using a 1–5 scale (1 – ‘not evident’ to 5 - ‘highly evident’) to describe the degree to which the lesson exhibits high levels of the element. Both programs were of moderate to high teaching quality and lowest scores were observed for Metalanguage, Student direction, Cultural knowledge and the use of Narrative. The QTM can be an effective tool to assess the teaching quality of nutrition education programs by examining classroom practice.